Regulation of NMDA receptors by phosphorylation - Chen, Bo-Shiun; Roche, Katherine W. (Neuropharmacology, 2007)
N-Methyl- d-aspartate (NMDA) receptors are critical for neuronal development and synaptic plasticity. The molecular mechanisms underlying the synaptic localization and functional regulation of NMDA receptors have been the subject of extensive studies. In particular, phosphorylation has emerged as a fundamental mechanism that regulates NMDA receptor trafficking and can alter the channel properties of NMDA receptors. Here we summarize recent advances in the characterization of NMDA receptor phosphorylation, emphasizing subunit-specific phosphorylation, which differentially controls the trafficking and surface expression of NMDA receptors.